Bordetella pertussis antigens encapsulated into N-trimethyl chitosan nanoparticulate systems as a novel intranasal pertussis vaccine. Issue 1 (4th December 2019) - Najminejad, Hamid; Kalantar, Seyed Mehdi; Mokarram, Ali Rezaei; Dabaghian, Mehran; Abdollahpour-Alitappeh, Meghdad; Ebrahimi, Seyyed Mahmoud; Tebianian, Majid; Fasihi Ramandi, Mahdi; Sheikhha, Mohammad Hasan
Abstract: The mucosal immune system serves as the first line of defense against Bordetella pertussis . Intranasal vaccination, due to its potential to induce systemic and mucosal immune responses, appears to prevent the initial adherence and colonization of the bacteria at the first point of contact. In the present study, two B. pertussis antigens, pertussis Toxoid (PTd) and Filamentous hemagglutinin (FHA), which play a very significant role in virulence and protection against pertussis, were encapsulate into N-trimethyl chitosan (TMC) nanoparticulate systems. After preparation of TMC nanoparticles (NPs), the NPs were characterized and their ability to induce efficient immune responses against B. pertussis was studied in a mouse model. Our findings showed that PTd + FHA-loaded TMC NPs have strong ability to induce IL-4, IL-17, IFN-γ, IgG, and IgA in the mouse model. Results from this study suggest that nasal administration of the PTd + FHA-loaded TMC NPs induced not only a systemic immune response but also a local mucosal response, which may improve the efficacy of pertussis prevention through respiratory tract transmission.